2002
DOI: 10.1094/cchem.2002.79.4.518
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Roll Fluting Disposition and Roll Gap on Breakage of Wheat Kernels During First‐Break Roller Milling

Abstract: Cereal Chem. 79(4):518-522Breakage of wheat kernels during first-break roller milling depends on many factors, including the disposition of the fluted rolls: sharp-to-sharp, sharp-to-dull, dull-to-sharp, or dull-to-dull. Wheat kernel breakage under different dispositions during milling was studied using high-speed video imaging. The results show significant slippage between kernels and the flutes when a dull working angle is used, especially when the dull angle is on the fast roll. Experiments were conducted t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 6 publications
(11 reference statements)
3
23
0
Order By: Relevance
“…The effects of roller milling parameters on oat breakage were investigated using the versatile Satake STR-100 test roller mill (Satake Corporation, Hiroshima, Japan) Fang & Campbell, 2002, 2003, using a feeding rate equivalent to 300 kg h À1 , and fitted with either corrugated or smooth rolls. All rolls were manufactured to industrial configurations for wheat flour milling, having diameters of 250 mm, but only 100 mm in length (compared with 1000 mm typically for industrial roller mills).…”
Section: Dry Milling Equipmentmentioning
confidence: 99%
“…The effects of roller milling parameters on oat breakage were investigated using the versatile Satake STR-100 test roller mill (Satake Corporation, Hiroshima, Japan) Fang & Campbell, 2002, 2003, using a feeding rate equivalent to 300 kg h À1 , and fitted with either corrugated or smooth rolls. All rolls were manufactured to industrial configurations for wheat flour milling, having diameters of 250 mm, but only 100 mm in length (compared with 1000 mm typically for industrial roller mills).…”
Section: Dry Milling Equipmentmentioning
confidence: 99%
“…This can be attributed to the difference in the hardness index of the different wheat classes. SRW wheat kernels, having the lowest hardness index, break into a greater proportion of smaller particles compared to hard wheat kernels (Fang and Campbell, 2002). Cohesion and agglomeration were not as evident in the HRW and HRS flours as they were in the SRW flour.…”
Section: Particle Size and Particle Size Distributionmentioning
confidence: 79%
“…Subsequently, Fang (1995) found that feed rate played the most crucial role during first break grinding. In a similar study, Fang and Campbell (2002) found that using a dullto-dull roll disposition for first break milling gave a Ushaped distribution of particle size, while a sharp-to-sharp disposition gave a straight-line distribution for first break mill streams. These studies indicated the important effects of roll parameters on flour extraction percentage.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The value of q 2 (x) is found by integrating the mass of outlet particles of size x created by any given inlet particle of size D, multiplied by the mass of inlet particles of size D. Assuming that only breakage not aggregation occurs, outlet particles of size x cannot be created from inlet particles of size D < x, so the integration takes place over the range of inlet particles for D P x. However, in the later papers (Fang & Campbell, 2003a, 2003b the authors corrected the limits of the integration (D = 0 instead of D = x) considering the fact that, particularly under dull-to-dull disposition, under the compressive crushing forces, it is entirely possible for a wheat kernel to break so as to produce flattened bran flake with dimensions larger than the kernel from which it came (Fang & Campbell, 2002a, 2002b. Secondly, the dimensions of the wheat kernel (D) and dimension of the broken particle (x) are measured in different ways, so they are not comparable.…”
Section: The Breakage Matrix Approachmentioning
confidence: 99%